The association between Vapor Pressure Deficit and arthritis: Evidence from a 10-year longitudinal study of middle-aged and elderly Chinese adults - Damei Ye; Shuchao Ye; Changyi Lin; Dongming Lu; Xuelan You; Chaoyan Xu; Yongyang Wu (PLoS ONE, 2026)
Objective To investigate the association between vapor pressure deficit (VPD) and arthritis in middle-aged and older Chinese adults. Methods This study utilized data from the China Health and Retirement Longitudinal Survey (CHARLS) spanning the years 2011–2020. Participants without arthritis in 2011 were selected as the study population, with VPD designated as the primary exposure factor and newly diagnosed arthritis cases as the outcome variable. Logistic regression models were used to estimate the association between VPD and incident arthritis. Restricted cubic spline (RCS) analyses were conducted to assess potential nonlinearity. Subgroup analyses were performed to examine effect heterogeneity across population subgroups. Results A total of 4615 subjects were included, and a total of 1317 subjects were reported to be diagnosed with arthritis during approximately 10 years of follow-up (2011–2020). The VPD level in the arthritis group was lower than that in the non-arthritis group (5.184 ± 0.828 vs 5.291 ± 0.818, p < 0.001). All logistic regression models showed that VPD was linearly related to the incidence of arthritis, and the relationship remained consistent even when VPD was categorized. RCS analysis showed that the incidence of arthritis decreased significantly with increasing VPD (p < 0.05), especially when VPD was lower than 5.28. Subgroup analysis indicated that VPD exerted a stronger protective effect against arthritis among rural residents (p for interaction = 0.006). Conclusion VPD was found to be negatively associated with the incidence of arthritis among middle-aged and elderly populations, with a particularly stronger effect observed in rural residents. These findings highlight VPD as an environmental factor associated with arthritis and may help improve understanding of environmental influences on arthritis development.